Pandemic, Poverty, and Inequality : Evidence from India - Bhalla, Surjit (IMF Working Papers; Working Paper, 2022)
The paper presents estimates of poverty [extreme poverty PPPD 1.9 and PPPD 3.2] and consumption inequality in India for each of the years 2004-5 through the pandemic year 2020-21. These estimates include, for the first time, the effect of in-kind food subsides on poverty and inequality. Extreme poverty was as low as 0.8 percent in the pre-pandemic year 2019, and food transfers were instrumental in ensuring that it remained at that low level in pandemic year 2020. Post-food subsidy inequality at .294 is now very close to its lowest level 0.284 observed in 1993/94.